Model Dinamis Sistem Ketersediaan Daging Sapi di Provinsi Jawa Timur - Nabillah Ammaryl Ulfah; Rudi Wibowo (UNEJ e-Proceeding, 2018)
Beef production in East Java has decreased due to the decrease in the number of cattle slaughtered and the desire of farmers to sell or cut cattle. The decline of beef production in East Java is not compare with the increasing consumption of beef each year. This condition will affect the beef availability in East Java in the future. The aims of this research are (1) Beef availability system in East Java, (2) Dynamic model of beef availability in East Java, and (3) Behavior of beef availability in East Java in the future. The research location was determined purposively (Purposive Methods) in East Java. Sampling using multistage sampling technique. The research methond used descriptive analytic method. Data analysis of beef availability system in East Java by descriptive method while the dynamic model of beef availability in East Java by conceptual model, model formulation, and validity test. Data analysis of behavior of beef availability by forecasting and simulation. The results showed: (1) The system of beef availability in East Java Province consisted of two subsystems namely supply subsystem and need subsystem. (2) The system model of beef availability in East Java Province which was developed with a dynamic system approach can be able to represent the system of beef availability in real terms. (3) Behavior of beef availability based on simulation I, the beef availability has decreased. (4) Behavior of beef availability based on simulation II, the behavior of beef availability has increased. (5) Behavior of beef availability in East Java Province based on simulation III has increased